Procalcitonin use for shorter courses of antibiotic therapy in suspected early-onset neonatal sepsis: are we getting there? - Gkentzi, Despoina; Dimitriou, Gabriel (Journal of Thoracic Disease; Vol 9, No 12 (December 29, 2017): Journal of Thoracic Disease, 2017)
Antibiotic overuse and subsequently infections caused by antibiotic resistant pathogens are a worldwide problem that according to the 2014 WHO report “threatens the achievements of modern medicine” (1). In the Neonatal Intensive Care Units (NICUs), antimicrobial use does undoubtedly influence the types of pathogens involved in neonatal sepsis as well as their resistance patterns (2). In addition to that, there is now overwhelming and accumulating evidence that antibiotic treatment in early life affects the neonatal microbial flora and leads to long-term consequences. The Centers for Disease Control and Prevention has initiated in 2011 a campaign to prevent antimicrobial resistance in healthcare settings (3) with emphasis on antimicrobial stewardship interventions. Antimicrobial stewardship is recognized as a critical patient safety and quality imperative which aims at optimizing clinical outcomes while minimizing the emergence of antimicrobial resistance and preserving the activity of the existing agents (4). Several antimicrobial stewardship strategies in NICUs have been proposed (5,6) and include interventions for improvement in the diagnosis of neonatal sepsis. The signs and symptoms of sepsis in infants are non-specific and may mimic the presentations of a non-infectious process but it is difficult not to treat with antibiotics for suspected sepsis when these symptoms appear. In addition, culture-negative sepsis is a common reason for antibiotic prescribing in NICUs. The use of biomarkers (7-9) such as C reactive protein (CRP), procalcitonin (PCT), interleukin